Al plasmon-enhanced diamond solar-blind UV photodetector by coupling of plasmon and excitons. (28th July 2016) - Shi, Xiaoqin; Yang, Zhengming; Yin, Shichen; Zeng, Haibo
Abstract : Localised surface plasmon (LSP) enhanced metal-semiconductor-metal interdigital solar-blind UV photodetector was fabricated by assembling of Al crescent-shaped arrays on boron-doped homoepitaxial diamond thin films. The spectral responsivity at 225 nm is about 28 m A/W biased at 5 V, which is over 10-fold more than that of bare diamond detector. The photodetector exhibits a rejection ratio up to 10 3 between 225 and 280 nm light. These observations can be attributed to near-field optical coupling between Al LSPs and diamond excitons through the improved optical absorption in the semiconductor layer. The complementary optical properties of metal Al nanostructures and diamond semiconductor make them attractive components for solar-blind UV photodetectors.